UJI EFEKTIVITAS ANTI BAKTERI EKSTRAK BIJI PEPAYA (Carica papaya L.) TERHADAP KELANGSUNGAN HIDUP IKAN NILA (Oreochromisniloticus) PASCA INFEKSI Aeromonas hydrophila - Kherma Levia; Saptono Waspodo; Baiq Hilda Astriana (Jurnal Perikanan Unram, 2021)
The rise of tilapia fish cultivation cannot avoid the application of high cultivation intensification. This can have a negative impact, one of which was the onset of Motile Aeromonas Septicaemia (MAS). Motile Aeromonas Septicaemia (MAS) was one of the diseases that can attack tilapia, this disease was caused by the bacterium Aeromonas hydrophyla. The study aimed to determine the effect of the use of pepaya seed extract (Carica papaya L.) on the survival of tilapia fish, tilapia growth and the profile of red blood cells of tilapia fish infected with A. hydrophila bacteria. The research method used was an experimental method with a completely randomized design (CRD) while the treatments are P1 (immersion with a concentration of 20%), P2 (30%), P3 (40%), P4 (50%) carried out for 30 days. The results showed the highest survival in the P3 treatment which is 66.66% and the lowest is P0 which is 13.33%, red blood test results show healthy fish blood on average above 30x10? cells / mm³ while sick fish that have been infected with A. hydrophila bacteria point to an average of above 5x10? cells / mm³ and fish in the treatment of P1, P2, P3, and P4 that have been soaked using pepaya seed extract and maintained for 14 days show blood test results above 25x10? cells / mm³ while fish that are not soaked show the results of calculations of 17.4x10? cells / mm³. The conclusion of this study was that P2 treatment with a dose of 30% was recommended for the survival rate of tilapia fish. P1 with a dose of 20% with the administration of pepaya seed extract has a real effect on the number of red blood cells of tilapia fish. As for the absolute long growth and absolute weight of tilapia fish, the immersion of pepaya seed extract has no real effect.